Endoscopy waiting times and impact of the two week wait scheme on diagnosis and outcome of upper gastrointestinal cancer - Spahos, T (BMJ Group, 2005)
The NHS has introduced the two week wait scheme to detect upper gastrointestinal cancers at an early stage and improve survival rates The aim of this study was to assess the impact of this scheme and changes in endoscopy waiting times on tumour stage and resection rates over a four year period. Data were analysed prospectively for all patients diagnosed with oesophagogastric cancer between September 1998 and September 2002 and from those referred under the two week wait scheme since its introduction in 2000. Of those tumours diagnosed by this scheme (15%) only 5% were early disease (stage 1 or 2). Patients with early cancer, mainly diagnosed by routine gastroscopy, do not present with symptoms meeting the two week wait criteria. An increase in the resection rates for early disease will most probably be seen with a reduction in routine endoscopy waiting times.